2003
DOI: 10.1074/jbc.m300401200
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol Impairs Insulin-stimulated Neuronal Survival in the Developing Brain

Abstract: Gestational exposure to ethanol causes fetal alcohol syndrome, which is associated with cerebellar hypoplasia. Previous in vitro studies demonstrated ethanol-impaired neuronal survival with reduced signaling through the insulin receptor (IR␤). We examined insulin signaling in an experimental rat model of chronic gestational exposure to ethanol in which the pups exhibited striking cerebellar hypoplasia with increased apoptosis. Immunoprecipitation and Western blot analyses detected reduced levels of tyrosyl-pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
166
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(182 citation statements)
references
References 65 publications
16
166
0
Order By: Relevance
“…1), as reported earlier [23]. Although the upstream events triggered by ethanol, which leads to caspase-3 activation in the brain, have not been fully elucidated, involvement of the PI3K/Akt pathway has been implicated [4,[8][9][10]. We found that ethanol reduced phospho-Akt and phospho-GSK-3β levels without changing the levels of Akt and GSK-3β at 4 h after the first ethanol injection (Fig.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…1), as reported earlier [23]. Although the upstream events triggered by ethanol, which leads to caspase-3 activation in the brain, have not been fully elucidated, involvement of the PI3K/Akt pathway has been implicated [4,[8][9][10]. We found that ethanol reduced phospho-Akt and phospho-GSK-3β levels without changing the levels of Akt and GSK-3β at 4 h after the first ethanol injection (Fig.…”
Section: Resultssupporting
confidence: 80%
“…Previous studies using cultured neurons indicate that ethanol perturbs functions of neurotrophic factors (such as brain-derived neurotrophic factor and insulin-like growth factor-I) probably through blockade of NMDA receptors [7][8][9] leading to the inhibition of PI3K [8,9]. The suppression of Akt [4] and activation of GSK-3 [10], downstream effects of PI3K inhibition, have also been reported in the developing brain exposed to ethanol. Our recent study showed that apoptotic neurodegeneration in P7 mice induced by acute ethanol exposure was accompanied by inactivation of Akt and activation of GSK-3β, which was indicated by decreases in phosphorylation levels of both protein kinases [11].…”
Section: Introductionmentioning
confidence: 99%
“…The primary hormones regulating lipolysis are catecholamines, which initiate lipolysis by the stimulation of ␤-adrenergic receptors, and insulin, which inhibits catecholamine-induced lipolysis (4). Chronic ethanol exposure disrupts both G proteinand insulin-dependent signal transduction in a variety of cell types, including adipocytes (5)(6)(7)(8). For example, we have demonstrated that ethanol feeding for 4 weeks decreases ␤-adrenergic receptor-stimulated lipolysis (9) and suppresses insulinstimulated glucose uptake in isolated adipocytes (10,11).…”
mentioning
confidence: 99%
“…Similar effects of serum withdrawal were also seen in cultured Neuroblastoma-2a cells [45]. Thus it seems that the reduction in PTEN expression to alcohol during gestation [47]. In this model the mice showed marked cerebellar hypoplasia and cell death indicating a correlation of PTEN with neuronal death [47].…”
Section: Pten and Neuronal Apoptosismentioning
confidence: 48%